Analisis Strategi Pengelolaan Sampah Berbasis Pengurangan (Reduksi) di Kecamatan Medan Helvetia Kota Medan - Koilola, Farakh Yolanda; Hadinugroho, Dwi Lindarto; Thoha, Achmad Siddik (Jurnal Ilmiah Global Education, 2024)
This research aims to analyze reduction-based waste management strategies in Medan Helvetia District, Medan City. The method used is qualitative with a survey approach and using SWOT and AHP analysis. This research began by identifying waste reduction efforts that had been carried out by residents of Medan Helvetia District and then a Focus Group Discussion (FGD) was carried out which resulted in 3 activity targets to be developed, namely (1) strategies to increase community participation to join environmental care communities; (2) strategy to improve the performance of waste banks, and (3) strategy to implement the circular economy concept in waste management to support the improvement of the people's economy. Based on the results of the SWOT analysis, the appropriate strategy for realizing the first activity target is the integration of the waste management education program with the TP PKK work program as well as providing waste reduction information on social media and banners in each sub-district. The priority target for the second activity is placing outlets receiving segregated waste in strategic location in the sub-district as well as waste bank management training, and the third priority strategy target, namely partner collaboration and capital assistance as well as assistance with composter equipment to produce organic fertilizer. The results of the AHP analysis show that the priority strategy in waste management based on reduction is increasing community participation to join environmental care communities with a weight value of 0.446 with an inconsistency value of 0.00001. This research shows that to increase community participation, continuous education is needed to be able to sort organic and inorganic waste, as well as disseminate information and waste reduction campaigns on social media and banners in each sub-district.